Diversity and coexistence are influenced by time‐dependent species interactions in a predator–prey system. (3rd April 2020) - Karakoç, Canan; Clark, Adam Thomas; Chatzinotas, Antonis
Abstract: Although numerous studies show that communities are jointly influenced by predation and competitive interactions, few have resolved how temporal variability in these interactions influences community assembly and stability. Here, we addressed this challenge in experimental microbial microcosms by employing empirical dynamic modelling tools to: (1) detect causal interactions between prey species in the absence and presence of a predator; (2) quantify the time‐varying strength of these interactions and (3) explore stability in the resulting communities. Our findings show that predators boost the number of causal interactions among community members, and lead to reduced dynamic stability, but higher coexistence among prey species. These results correspond to time‐varying changes in species interactions, including emergence of morphological characteristics that appeared to reduce predation, and indirectly facilitate growth of predator‐susceptible species. Jointly, our findings suggest that careful consideration of both context and time may be necessary to predict and explain outcomes in multi‐trophic systems. Abstract : Few studies have resolved how temporal variability in species interactions influences community assembly and stability. We addressed this challenge in experimental microbial microcosms by employing empirical dynamic modelling tools. Our work provides evidence that the temporal dynamics of species in response to predation and competition can be highly variable, suggesting both context and time resolution may be necessary to understand the stability of multi‐trophic systems.